Association study between killer immunoglobulin‐like receptor polymorphisms and ankylosing spondylitis disease: An updated meta‐analysis. (5th November 2018) - Rezaei, Ramazan; Mostafaei, Shayan; Aslani, Saeed; Jamshidi, Ahmadreza; Mahmoudi, Mahdi
Abstract: Background: Several genetic studies have assessed the association between polymorphisms in killer immunoglobulin‐like receptors (KIR) genes and susceptibility of individuals to ankylosing spondylitis (AS), but the findings have been inconclusive and incongruous. Therefore, we conducted this meta‐analysis of all case‐control studies meeting the inclusion criteria for obtaining an exact conclusion of the effect of KIR polymorphisms on the risk of AS. Methods: A systematic literature search was conducted in electronic databases, including Scopus web of science, ScienceDirect, and PubMed to find all eligible studies exploring the association between KIR polymorphisms and the risk of AS, prior to June 2017. Pooled odds ratios (OR) and their corresponding 95% CIs were used to evaluate the strength of the association between KIR polymorphisms and the risk of AS. Results: A total of 16 case‐control studies, encompassed in 12 papers, with 1770 cases and 2907 healthy subjects were included in the meta‐analysis. This meta‐analysis revealed three significant positive associations of 2DS1, 2DS5, and 3DS1 with susceptibility to AS, while two significant negative associations of 2DL2 and 2DS2 with susceptibility to AS were identified. In the subgroup analysis based on human leukocyte antigen (HLA)‐B*27 positive patients and healthy subjects, results indicated that there were four significant positive associations between 2DL5, 2DS4, 2DS5, 3DS1 polymorphisms and susceptibility to AS in HLA‐B*27‐positive patients; a significant negative association of 3DL1 in HLA‐B*27‐positive patients was found. Conclusions: While 2DS1, 2DS5, and 3DS1 polymorphisms increased AS risk, 2DL2 and 2DS2 polymorphisms were associated with reduced AS susceptibility.